ANALISIS AKSIOLOGI FILSAFAT PENDIDIKAN ISLAM DALAM MENDALAMI NILAI AKIDAH, NILAI IBADAH DAN NILAI PENDIDIKAN AKHLAK - Maulana El-Yunusi, Muhammad Yusron (Universitas Islam Negeri Sumatera Utara Medan, 2024)
Axiology is a branch of philosophy that deals with values and sets ultimate goals in the teaching and learning process. In the context of Islamic educational philosophy, axiology is not only rooted in worldly aspects, but also derives from the revelation sent down by Allah. This article aims to explore three main values that create an axiological structure in Islamic education, namely the values of faith, worship, and character building. This study applies a literature study method which involves conducting a comprehensive review of various sources. The data sources sought came from a number of books, articles, journals. The research findings show a correlation and mutual support between these values. The value of faith serves as the foundation for understanding existence and knowledge, which directs an individual's belief in one God. The value of worship is a representation of this belief, so that activities in education can be used as a means of devotion to Allah SWT. In addition, the value of moral education serves as the result and means of these two values, with the aim of shaping noble character in students. The conclusion of this article emphasizes the importance of integrating these three values into educational practice, which is also a necessity.